2014
DOI: 10.1017/s000186780000759x
|View full text |Cite
|
Sign up to set email alerts
|

Probability Distribution Function for the Euclidean Distance Between Two Telegraph Processes

Abstract: Consider two independent Goldstein-Kac telegraph processes X 1 (t) and X 2 (t) on the real line R. The processes X k (t), k = 1, 2, describe stochastic motions at finite constant velocities c 1 > 0 and c 2 > 0 that start at the initial time instant t = 0 from the origin of R and are controlled by two independent homogeneous Poisson processes of rates λ 1 > 0 and λ 2 > 0, respectively. We obtain a closed-form expression for the probability distribution function of the Euclidean distance ρ(t) = |X 1 (t) − X 2 (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is clear that 0 < ρ(t) < (c 1 + c 2 )t with probability 1 for any t > 0, that is, the open interval (0, (c 1 + c 2 )t) is the support of the distribution of process ρ(t). Note that, in contrast to the one-dimensional case (see [2]), the distribution of the Euclidean distance (4.1) is absolutely continuous in the interval (0, (c 1 + c 2 )t) and does not contain any singular component. This means that probability distribution function (4.2) is continuous for r ∈ R and does not have any jumps.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It is clear that 0 < ρ(t) < (c 1 + c 2 )t with probability 1 for any t > 0, that is, the open interval (0, (c 1 + c 2 )t) is the support of the distribution of process ρ(t). Note that, in contrast to the one-dimensional case (see [2]), the distribution of the Euclidean distance (4.1) is absolutely continuous in the interval (0, (c 1 + c 2 )t) and does not contain any singular component. This means that probability distribution function (4.2) is continuous for r ∈ R and does not have any jumps.…”
Section: Resultsmentioning
confidence: 94%
“…The method of obtaining a formula for Φ(r, t) is different from that used in the onedimensional case (see [2]). While in [2] the method is based on evaluating the probability the particle to be located in a r-neighbourhood of the other one, in the multidimensional case such approach is impracticable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the shifted time derivative of the transition density satisfies the telegraph equation with doubled parameters 2c and 2λ. A functional relation connecting the distributions of the difference of two independent telegraph processes with arbitrary parameters and of the Euclidean distance between them, was given in [18,Remark 4.4].…”
Section: Sum and Difference Of Two Telegraph Processesmentioning
confidence: 99%
“…However, to the best of the author's knowledge, there exist only a few works where a system of several telegraph processes is considered. A closed-form expression for the probability distribution function of the Euclidean distance between two independent telegraph processes with arbitrary parameters was derived in [18]. The explicit probability distribution for the sum of two independent telegraph processes with the same parameters, both starting from the origin of R, was obtained in [17].…”
Section: Introductionmentioning
confidence: 99%